Cultural Da’wah: Analyzing Islamic Education Values in Kubro Siswo Art Magelang - Miftachurrozaq, Tahmid; Suyadi, Suyadi; Bustam, Betty Mauli Rosa; Wantini, Wantini; Perawironegoro, Djamaluddin (Jurnal Dakwah Risalah, 2023)
The dichotomy of religion and culture has denied acculturation from various societal elements. This study aims to analyze the values of Islamic education and its role in cultural da'wah in the art of Kubro Siswo. This research uses a descriptive qualitative approach with field study research. The results indicate that Kubro Siswo is an art form that integrates Islamic teachings with local culture, encouraging the development and co-existence of hadith in society. Kubro Siswo has Islamic educational values including the values of aqidah, worship, morals, and socio-culture contained in the verses of the songs chanted and community behavior. Kubro Siswo has a role in preaching culturally. Some of its advantages and application as a medium of cultural da'wah through appreciation of art, as a message of harmony between (habluminallah) and (habluminannas), fostering a culture of multiculturalism, as a form of intuitive intelligence and a natural message of humans can be conveyed through art, as education to foster noble behavior and ethics.